Digital homiletics: the theology and practice of online preaching - Yang, Sunggu (Working preacher books, 2024)
"Digital Homiletics demystifies the art of online preaching and helps readers understand both the why and how of engaging listeners in digital formats. After laying a concise and accessible theological foundation, Yang shares ten methods for effective digital preaching. Readers will encounter concrete tips and advice for sharing God's Word online"--